Radiation sensitive MOSFETs irradiated with various positive gate biases. Issue 1 (December 2021) - Ristic, Goran S.; Ilic, Stefan D.; Duane, Russell; Andjelkovic, Marko S.; Palma, Alberto J.; Lallena, Antonio M.; Krstic, Milos D.; Stankovic, Srboljub J.; Jaksic, Aleksandar B.
ABSTRACT: The RADiation sensitive metal-oxide-semiconductor field-effect-transistors (RADFETs) were irradiated with gamma rays up to absorbed dose of 110 Gy(H2 O). The results of threshold voltage, VT, during irradiation with various positive gate biases showed the increase in VT with gate bias. The threshold voltage shift, Δ VT, during irradiation was fitted very well. The contributions of both the fixed traps (FTs) and switching traps (STs) during radiation on Δ VT were analyzed. The results show the significantly higher contribution of FTs than STs. A function that describes the dependence of threshold voltage shift and its components on gate bias was proposed, which fitted the experimental values very well. The annealing at the room temperature without gate bias of irradiated RADFETs was investigated. The recovery of threshold voltage, known as fading, slightly increase with the gate bias applied during radiation. The Δ VT shows the same changes as the threshold voltage component due to fixed states, Δ Vft, while there is no change in the threshold voltage component due to switching traps, Δ Vst .